Penerapan Metode Peramalan Moving Average dan Exponential Smoothing untuk Menyusun Perencanaan Produksi: Survei pada UMKM Pembuatan Bordir dan Pakaian, Nining Collection di Ciamis - Dita Ratna Kania; Suci Putri Lestari; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and predict the number of products that the company must make and estimate from the sales data owned by UMKM Nining Collection for the period January 2019 – December 2021. The method of data collection in this study is by direct observation of UMKM Nining Collection using techniques such as interviews,observations,and documentation. The analysis tool is carried out using forecasting methods such as moving average and exponential smoothing. The results of the forecasting analysis show that the 3 period moving average method is better for use in companies because it has the smallest error value. The company should follow the calculation of the forecasting method with a 3 period moving average so that it is able to predict and prepare production plans.